FUNCTIONAL GRAMMAR (An Introduction to Metafunctional Components of Language) - Panggabean, Christina I.T. (OKARA: Jurnal Bahasa dan Sastra, 2011)
Functional Grammar describes grammar in functional terms in which a language is interpreted as a system of meanings. The language system consists of three macro-functions known as meta-functional components: the interpersonal function, the ideational function, and the textual function, all of which make a contribution to the structure of a text. The concepts discussed in Functional Grammar aims at giving contribution to the understanding of a text and evaluation of a text, which can be applied for text analysis. Using the concepts in Functional Grammar, English teachers may help the students learn how various grammatical features and grammatical systems are used in written texts so that they can read and write better.